국내 수은 연구 동향 및 관리 현황 - 정종수; 심상규 (한국대기환경학회, 2009)
This paper reviews the current status of mercury research on exposure and contamination, mercury emissions, emission limits and control technologies, long-range transport and deposition research, and mercury management policy in Korea. According to a monitoring of the Ministry of Environment and the Ministry of Health and Welfare, blood mercury levels among Koreans are 5~8 times higher than those of U.S. and Germany. The most dominant source of exposure to mercury is through dietary intake. Emissions of mercury from coal-fired power plants are estimated 8.93 ton/year in 2004. Emissions of mercury from other important sources, such as waste incineration, steel and cement manufacturing and non-ferrous metal smelting operations are to be further investigated. A study on long-range transport of mercury suggests that the dry deposition flux over the Yellow Sea was much greater than those for other oceans. As a whole, the amounts of wet depositions of nitrogen and sulfur were 1.9 and 1.5 times larger than the amounts of dry depositions in each species, respectively. Substantial influence from China caused by high emissions in East China and westerly wind was possibly suggested. However, the influence from nitrogen emission in Korea was also confirmed. Korean Government has already adopted stringent emission limits on mercury for incinerators and boilers in 2005. However, emission limits for coal-fired power plants and non-ferrous metal smelters are rather relaxed. As the above mentioned two sources can be two most important sources of mercury emissions, control strategy for those sources are to be considered.